Aortic recoarctation and pseudoaneurysm five decades after repair. Issue 11 (17th August 2019) - Lim, Brian; Forest, Stephen J.; Schultz, Megan L.; Lipsitz, Evan; Michler, Robert E.
Abstract: Background: Coarctation of the aorta is a congenital cardiac defect characterized by a narrowing of the proximal thoracic aorta. Despite excellent long‐term results, surgical repair is rarely complicated by recoarctation. Methods/Results: We describe a case with the longest time to reintervention to date, featuring surgical repair of delayed aortic recoarctation and pseudoaneurysm 53 years after the initial operation. Discussion: This case emphasizes the need for lifelong surveillance in this patient population and exemplifies a multidisciplinary approach in evaluating treatment options of complex aortic pathology, including open and endovascular considerations.